Factors that favor tridimensional and hermetic obturation of root canal system - Marion, Jefferson J.C.; Batista, Déric Meschiari; Murata, Sueli Satomi [UNESP]; Souza, Valdir de [UNESP]; Holland, Roberto [UNESP] (My University, 2014)
Objective: This study aims at demonstrating the possibility and importance of filling different types of accessory canals in different teeth. Methods: The sample comprised 11 cases in which detailed knowledge of the inner anatomy of root canal systems associated with good use of the crown-down preparation technique - irrigation with 1% sodium hypochlorite and 17% trisodium EDTA for cleaning and removing smear layer - enabled different types of filling cement to drain. Results: Endométhasone, SealapexTM and Zinc Oxide - Eugenol filling cements proved to be efficient in root canal filling with the aid of the Tagger technique. Conclusion: It could be concluded that a combination of knowledge about anatomy, techniques and substances yield satisfactory results in 3D filling and hermetic seal of root canals, which leads to successful endodontic treatment.
Keywords: Endodontics; Root canal filling; Transverse anatomy